News and Notes From the 2009 Carrier Advisory Committee Meeting: Medical Necessity, Off-Label Chemotherapy, and More - McAneny, Barbara (American Society of Clinical Oncology, 2009)
A discussion of two compelling topics at this summer's Hematology-Oncology Carrier Advisory Committee Network Meeting: coverage for off-label uses of anticancer drugs and medical necessity for oral versus intravenous antiemetics.